2005
DOI: 10.1515/polyeng.2005.25.4.305
|View full text |Cite
|
Sign up to set email alerts
|

Extensibility of EVA Based Nanocomposites

Abstract: The structure and deformation characteristics of ethylene-vinyl acetate (EVA)-layered silicate nanocomposites were studied using steady shear and extensional rheology. EVAs with VA contents of 18% and 28% by weight and a commercially modified montmorillonite clay were melt compounded in a twin-screw extruder. Nanocomposites of 2.5%, 5% and 7.5% by weight were produced. WAXS measurements have revealed that EVA chains had intercalated into the silicate layers and expanded the interlayer distance. TEM showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…A smooth surface is observed for EVA/3 wt% C10A film ( Fig. 16,26,31 For our films, this lack of C10A dispersion in the EVA matrix can be explained by the fact that the VA group is attached to the unmodified region of clay platelets which present a hydrophilic character, as referenced in the literature. In contrast, a roughness of film is noted at higher nanoclay loadings ( Fig.…”
Section: Nanocomposite Structuresupporting
confidence: 63%
See 1 more Smart Citation
“…A smooth surface is observed for EVA/3 wt% C10A film ( Fig. 16,26,31 For our films, this lack of C10A dispersion in the EVA matrix can be explained by the fact that the VA group is attached to the unmodified region of clay platelets which present a hydrophilic character, as referenced in the literature. In contrast, a roughness of film is noted at higher nanoclay loadings ( Fig.…”
Section: Nanocomposite Structuresupporting
confidence: 63%
“…2(a)), indicating a homogeneous dispersion of C10A in the polymer matrix. 26,31 Through the analysis of TEM micrographs of the nanocomposite films (Fig. 2(b) and (c)), attributable to agglomerated clay platelets.…”
Section: Nanocomposite Structurementioning
confidence: 99%
“…Nonetheless, in a study conducted by Prasad et al on exfoliated ethylene‐vinyl acetate/layered silicate nanocomposites, N 1 demonstrated an inverse relationship with filler contents; i.e., the magnitude of N 1 declined as the silicate filler content increased. They associated this behavior to the reduced mobility of polymer chains due to the enhanced interactions between silicate fillers and polymer chains .…”
Section: Resultsmentioning
confidence: 96%
“…The near independence of N 1 from filler content at all shear rates in intercalated PNCs has been associated with the intercalation of fillers in the composites, resulting from the preferential orientation of two‐dimensional nanofillers in the direction of flow which could diminish the effect of CC and CP interactions and their influence to elasticity . Nonetheless, in a study conducted by Prasad et al on exfoliated ethylene‐vinyl acetate/layered silicate nanocomposites, N 1 demonstrated an inverse relationship with filler contents; i.e., the magnitude of N 1 declined as the silicate filler content increased. They associated this behavior to the reduced mobility of polymer chains due to the enhanced interactions between silicate fillers and polymer chains .…”
Section: Resultsmentioning
confidence: 99%
“…Even though XRD analyses are useful in examining interlayer d-spacing of ordered layered silicate structures, they may fall short when no scattered intensity peaks are observed and such lack of peaks could be interpreted as exfoliation. Therefore, TEM has been regarded to be essential as it gives a direct evidence of what structure exists in the nanocomposite [23]. All the EVA40/clay nanocomposites were found to indicate individual dispersion of completely delaminated clay sheets in the EVA40 matrix from the TEM.…”
Section: Resultsmentioning
confidence: 99%